Experimental analysis of steel dissipative bracing systems for seismic upgrading - M. Mazzolani, Federico; Corte, Gaetano Della; D’Aniello, Mario (Journal of Civil Engineering and Management, 2009)
Energy dissipating devices, such as metallic ductile dampers, could represent one reliable system for seismic performance upgrading of reinforced concrete (RC) structures. This paper illustrates the significant improvement to the seismic response of RC structures equipped with dissipative bracing systems, such as eccentric braces (EBs) and buckling restrained braces (BRBs). In fact, the results of experimental tests carried out on two similar two‐storey one‐bay RC structures, respectively equipped with EBs and BRBs, are described. Referring to EBs, 3 lateral loading tests have been performed. Each test is characterized by shear links with bolted end‐plate connections. Different design criteria have been applied in the design of the connections. In the first test, capacity design criteria have not been considered. In the second test, a capacity design criterion has been applied, with a link shear over‐strength factor equal to 1.5. In the third test, a design criterion similar to the one adopted for the second test has been implemented, but with a larger over‐strength factor. In case of BRBs, two types of ‘only‐steel’ braces have been tested: one type was made using two buckling‐restraining rectangular tubes that are fully welded together with steel plates; the other type is detachable, being made again with two buckling‐restraining rectangular tubes but joined together by means of bolted steel connections. In both cases, the internal yielding core was a rectangular steel plate. The experimental results of both bracing systems are encouraging about the possibility to use these devices for improving the seismic resistance of existing RC structures. Stiprinamų pastatų seisminius poveikius slopinančių plieninių ryšinių sistemų eksperimentiniai tyrimai Santrauka. Didinant gelžbetoninių pastatų atsparumą seisminiams poveikiams, gali būti naudojami energiją sugeriantys metaliniai slopintuvai. Straipsnyje parodoma, kaip tokios slopinančios sistemos, kaip necentriniai ryšiai ir klupimą suvaržantys ryšiai, gali iš esmės gerinti pastato seisminę elgseną. Pateikiami dviejų panašių vienos angos gelžbetoninių pastatų su minėtaisiais ryšiais eksperimentiniai tyrimų rezultatai. Tyrimai parodė, kad abi suvaržymo sistemos gerina eksploatuojamų gelžbetoninių pastatų atsparumą seisminiams poveikiams. Reikšminiai žodžiai: klupimą varžantys ryšiai, laikomosios galios skaičiavimas, stamantrumas, necentriniai ryšiai, eksperimentiniai bandymai, atnaujinimas dėl seisminių poveikių. First Published Online: 14 Oct 2010